A Study of Product Innovation as a Catalyst for Customer Satisfaction and Trust - Samsul Arifin; Didit Darmawan (Jurnal Visi Manajemen, 2025)
This study aims to understand the effect of product innovation on customer satisfaction and trust, focusing on customers in the electronics sector. Product innovation is considered a strategic element capable of increasing customer utility, creating competitive advantage, and strengthening the relationship between companies and customers. Using a quantitative approach, data was collected through a survey to explore customer perceptions related to innovation, satisfaction, and trust. The results show that product innovation significantly affects customer satisfaction, especially through the relevance of the features offered, product quality, and adequate after-sales service. Customer trust in the company is also influenced by the success of product innovation to create real added value. This trust is formed through consistency in product quality and transparency in communication. This research implies that companies need to make innovation a strategic priority that is oriented towards customer needs. A deep understanding of customer preferences and expectations through market research and direct feedback is essential to support the innovation process. Effective communication to explain the benefits of innovation to customers should be part of the marketing strategy. With this approach, product innovation can be an instrument that increases customer satisfaction and trust, and creates long-term beneficial relationships.